Hearing Loss due to Noise Exposure and its Relationship with Hypertension in Peruvian Workers - Ramírez Saldaña, María Alejandra; Torres-Malca, Jenny Raquel; Zuzunaga-Montoya, Fiorella E.; Vera-Ponce, Víctor Juan; Cruz-Ausejo, Liliana; La Cruz-Vargas, Jhony A. De (International Journal of Statistics in Medical Research, 2022)
Introduction: Noise-induced hearing loss has been implicated in the genesis of several chronic conditions; however, its behavior concerning hypertension still raises doubts about it. Objective: to determine the association between hearing loss due to exposure to noise and the presence of hypertension in a sample of Peruvian workers. Methods: Cross-sectional analytical study. Secondary analysis of the occupational database of a Medical center in Lima, Peru. hypertension was measured by self-report and clinical method. Hearing loss was classified as none, mild, moderate and severe. For the regression analysis, Poisson was performed with robust variance, obtaining crude (PRc) and adjusted (PRa) prevalence ratios. Results: We worked with a total of 1987 participants. The prevalence of hypertension was 15.40% and hearing loss was 36.39%. For the multivariate regression analysis, a statistically significant association with hypertension was found in those with mild hearing loss (PRa=1.52; CI95% 1.06–2.10), moderate (PRa=2.70; CI95% 1,93–3.76) and severe (PRa=3.82; 95% CI 2.56–5.96), compared to those without hearing loss. Conclusions: Hearing loss due to exposure to occupational noise was associated with the presence of hypertension. Although this study is only a first overview of the relationship that both variables could have, it is recommended to continue promoting policies and awareness campaigns to prevent hearing loss in workers, and thus avoid complications related to it in the long term.